Collins, Francis S. ¿Cómo habla Dios? La evidencia científica de la fe - Francis S. Collins; Armando Rojas C. (Ideas y Valores)
Collins, Francis S. ¿Cómo habla Dios? La evidencia científica de la fe, 5a ed. Madrid: Temas de Hoy, 2009.